(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
Heat and moisture transfer occur simultaneously during the fish drying process. Continuous monitoring is necessary to ensure high quality fish drying. In this study, a digital system was designed to monitor parameters (Temperature (-400C±0.50C to 800C±0.50C), Relative Humidity (0 to 100%RH ±2%RH) and smoke concentration (200ppm to 5000ppm)) in the fish drying process in a dryer. A system engineering design approach with the use of Computer Aided Design (CAD) tools was used to establish the basic layout of the different sections of the system using Arduino UNO (based on ATmega328P), sensors, a Liquid Crystal Display (LCD), a micro SD card module and an alarm system. These components were integrated as an embedded system through the use of a compiler; Arduino integrated development environment (Arduino 1.8.7) and Proteus designer suit (Proteus 8.1 professional). The testing was done on the dryer for about 7Hours and 35minutes by monitoring the drying parameters. The results obtained showed that the virtual system modeler software provided a complete embedded digital laboratory for the simulation and implementation of the fish digital monitoring system. The microcontroller drawn is also able to accept, and execute the code produced with Arduino IDE connected to Proteus designer suit. The developed system works effectively in monitoring the drying parameters inside the drying chamber of a fish dryer with the ability to displayed, stored and retrieved the data for future use.